Penerapan Hand Painting Bunga Anggrek Bulan Khas Jawa Timur Pada Busana Modest - Silvani Mustika Prameswari (Corak, 2025)
Hand painting on textiles enhances aesthetic value and uniqueness in garments, especially in modest fashion, which emphasizes elegance and artistic details. The Orchid Moon flower motif from East Java was chosen as the main design element to reinforce cultural identity. The process includes motif exploration, fabric selection, and color application to ensure durability without diminishing motif beauty. The results show that this motif adds an exclusive and elegant impression while enhancing the visual appeal of modest fashion. This technique enriches design exploration and serves as an innovation for the local fashion industry with high artistic value.